Impacts of land use and climate changes on hydrological responses in a Peruvian Andean watershed - Saavedra, Danny (2025)
Hydrometeorological data from the Rontoccocha Ecohydrological Monitoring System and the Soil and Water Assessment Tool hydrological model were used. The results show that climate change has a more significant impact on water resources (up to 26% increase in mean annual runoff) than land use change (up to 1%). However, when combining both factors, the effects depend on the magnitude and dynamics with which each scenario influences hydrological processes. We find that MERESE has a high potential under changing conditions, since, through afforestation practices, it can increase groundwater (GWQ; 10–20%) and reduce surface runoff (SURQ; 10–60%). However, these effects could be improved considering the findings of this study. This research evaluated the impacts of land use and climate change on the hydrological responses of a high Andean watershed, as well as the relevance of the MERESE programme in the context of changing scenarios. The study was carried out in the Rontoccocha and Ccayllahuasi basins, which are the main water recharge zones supplying water sources for human consumption and irrigation in the city of Abancay. For this purpose, the SWAT hydrological model was used, which was calibrated and validated with data from the REMS and the PISCO database. Furthermore, 21 individual and combined scenarios of land use change and climate change were constructed and simulated in the SWAT model to analyse their effects on the hydrological processes in the basin.